Recent advances in synthesis of emerging MXenes photocatalysts: A systematic review - Ali, Md Mohshin; Hossen, Md. Arif; Azrina, Abd Aziz (Elsevier Ltd, 2025)
MXenes have emerged as a prominent area of research within the domain of nanomaterials, suggesting a potential transformation in material science technology. Their layered structure imparts distinctive properties suitable for a wide range of applications. Nevertheless, the existing synthesis methods pose a significant challenge in establishing MXenes as viable sustainable materials for future use. Researchers are progressively exploring novel synthetic routes to improve photocatalytic performance and environmental resilience. This systematic review provides a rigorous overview of recent advancements in the synthesis of emerging MXenes, highlighting their exclusive properties that make them promising candidates for various photocatalytic applications. The study utilized the PRISMA methodology for systematic literature reviews to avoid bias and collect information accurately. Peer–reviewed articles published in English from 2018 to 2024 were selected from two major primary databases. Based on the formulated logical search criteria, a total of 93 articles were chosen for critical review. The analysed literature showed that MXenes photocatalysts mostly utilized for atmospheric CO2 reduction, H2 evolution reactions, and pollutants degradation. Researchers are striving to explore novel synthesis strategies to improve the properties of MXenes. However, despite significant advancements in this area, the development of safer and more environmentally friendly etching methods for MXenes remains challenging for attaining large–scale production. This research comprehensively analyses findings from various studies to identify the main obstacles and opportunities in photocatalysis. The study also highlights the current barriers to facilitate the stability, scalability, and reproducibility of MXenes photocatalysts for sustainable energy and environmental remediation applications.